2021
DOI: 10.3389/fenvs.2021.734081
|View full text |Cite
|
Sign up to set email alerts
|

Taking Stock and Re-Examining the Role of Science Communication

Abstract: Eight science communication research projects have been funded by the European Commission since 2018. These projects are a response to one of the European Commission's 'Science with and for Society' (SwafS) funding calls -"SwafS-19: Taking stock and re-examining the role of science communication." Together these projects have received almost €10 million in research funding, and each has been affected to some extent by the COVID-19 global pandemic. This paper provides an overview of the eight projects, how they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…We have also shown that the co-design methodology is flexible and adaptable to different environments (face to face vs virtual, different languages and cultures) which can be very valuable for further replication, even during pandemic and physical lockdows [Roche, Arias et al, 2021].…”
Section: Lessons Learnedmentioning
confidence: 99%
“…We have also shown that the co-design methodology is flexible and adaptable to different environments (face to face vs virtual, different languages and cultures) which can be very valuable for further replication, even during pandemic and physical lockdows [Roche, Arias et al, 2021].…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Students gain an understanding of how science is taught and communicated, an awareness of how research policy and public perception are crafted, and a familiarity with the challenges arising at the interface of science and society. It draws together national developments, such as the growth of citizen science (Roche et al, 2021b), with international developments in the field of science communication (Roche et al, 2021a). While once considered an "emerging discipline" (Trench and Bucchi, 2010, p. 1), science communication is increasingly important in science education (Mercer-Mapstone and Kuchel, 2017) and guidance can now be found on how best to teach science communication across disciplines (Lewenstein and Baram-Tsabari, 2022).…”
Section: Curriculum Changesmentioning
confidence: 99%
“…From 2018-2020, the European Commission, through a funding call in the Science with and for Society (SwafS) pillar of Horizon 2020, the world's largest multinational research funding programme (Abbott, 2020), invited large-scale research proposals to take stock and re-examine the role of science communication (European Commission, 2020;Roche et al, 2021a). This was the first dedicated research funding call (rather than a "Coordination and Support Action") of its size offered by the European Commission for science communication research, and saw a total of eight projects funded (CONCISE, RETHINK, QUEST, TRESCA, NEWSERA, ParCos, ENJOI, and GlobalSCAPE), with an overall investment of almost €10 million (European Commission, 2022;Roche et al, 2023).…”
Section: Globalscape: a Global Study Of Science Communicatorsmentioning
confidence: 99%